ADMA: a specific biomarker for pathologic progress in diabetic microvascular complications?. (April 2016) - Jing, Zhiqiang; Kuang, Liqing; Wang, Yanping; He, Jiajia; Sun, Zilin; Liu, Naifeng; Yang, Jin
Background: This study highlights the role of glycated hemoglobin (HbA1c), asymmetric demethylargine (ADMA) and N -ϵ-(carboxymethyl)-lysine (CML) in different periods of progress in Type 2 diabetes, and identifies a pathomechanism-based biomarker that is linked not only to the metabolic progresses but also to the underlying angiopathic progresses.Methods: Peripheral blood samples from 100 healthy volunteers, 227 subjects with prediabetes, 173 subjects with Type 2 diabetes and 92 subjects with early diabetic microvascular complications were collected and analyzed for HbA1c, ADMA and CML.Results: Compared to HbA1c and CML, ADMA is the strongest independent predictor and a significantly discriminative receiver operating characteristics profile, clearly distinguishing those with early diabetic microvascular complications.Conclusions: ADMA maybe serve as a pathomechanism-based biomarker, predicting the progression of microvascular complications.